2005
DOI: 10.1007/s10257-004-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious experience in retail e-commerce: An inductive taxonomy of product evaluation support features

Abstract: In general, direct experience (touch, taste, use, and so on) of physical products is impossible in an online environment. Knowledge of the experience attributes of these goods must therefore be obtained via an intermediary (vicariously). Unfortunately, little has been published about how to design online retail systems that help customers evaluate physical products. This paper addresses that gap by (1) surveying a wide range of sites, and (2) evaluating the features found using a grounded, rigorous evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In the case of Taksim Square protests, vicarious experience was represented in tweets sharing others' personal experiences in protest efforts. Therefore, from a social media angle, vicarious experience may have been used more to convey a message (consistent with arguments by Smith et al, 2005) than for personal motivation to act.…”
Section: Social Media Influence and Vicarious Experiencementioning
confidence: 79%
See 1 more Smart Citation
“…In the case of Taksim Square protests, vicarious experience was represented in tweets sharing others' personal experiences in protest efforts. Therefore, from a social media angle, vicarious experience may have been used more to convey a message (consistent with arguments by Smith et al, 2005) than for personal motivation to act.…”
Section: Social Media Influence and Vicarious Experiencementioning
confidence: 79%
“…There are few studies applying vicarious experience to the online environment. Smith, Johnston, and Howard (2005) explored the concept in relation to e-commerce, and suggested that vicarious experience online comprises gaining ''experience attributes. .…”
Section: Power From Cognitionmentioning
confidence: 99%
“…This examination may take place in presence of the real product (direct inspection), through other channels (indirect one), or through a similar product, which the user considers purchasing. This stage is previous to the purchasing decision, in which either the most suitable product will be chosen or all products will be rejected (Smith et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The decision to use more advanced modes of representation could depend on the type of product in question and the aims of the company. In this sense and according to the classification proposed by Smith et al (2005), industrial products can be divided into two categories: ''value-expressive'' products and ''utilitarian'' ones. Value-expressive goods are selected based on what the products symbolise and what they express to others (Johar and Sirgy, 1991;Levy, 1959;Shavitt, 1992).…”
Section: Article In Pressmentioning
confidence: 99%
“…At least, they expect some sort of consulting efforts from the supplier side, such as product evaluation support features [42]. Besides asynchronous feedback and contact forms (contact data and email) and added-value information (FAQs/online discussion forums) [43], call-back or chat features (such as synchronous live web help, service and sales chat [4], [44]), and videoconferencing [12] are examples of more innovative forms of online support features providing advice on corporate websites.…”
Section: Literature Reviewmentioning
confidence: 99%